Disaster's Impact on Livelihood and Cultural Survival: Losses, Opportunities, and Mitigation by Michèle Companion (Ed.). Issue 3 (September 2016) - Rivera, Jason D.
Abstract : This essay reviews the edited volume, Disaster's Impact on Livelihood and Cultural Survival: Losses, Opportunities and Mitigation, by Michèle Companion. An overview of the book and the sections contained it are presented, and then a discussion of overarching themes is summarized. Finally, a discussion of recommendations for maintaining peoples' livelihoods and cultures in the aftermath of disasters are provided.